Progressive psychology and the question of race: Manganyi, N C (1990) Treachery and innocence: Psychology and racial difference in South Africa. Johannesburg: Ravan. ISBN 0-86975-419-X. - Swartz, Leslie (PINS-Psychology in Society, 2026)
This book opens with and has a its raison d'etre an important challenge to progressive psychology. Manganyi notes that progressive South African intellectuals "are wedded to questions of class" (p1), and argues that racism "continues to be the Achilles' heel of the discipline in South Africa" (p1). He argues further that black psychologists are marginalised even within progressive psychology.